Healthy at Work? Evidence from a Social Experimental Evaluation of a Firm-Based Wellness Program - Marianne Simonsen; Lars Skipper (CESifo GmbH, 2024)
We employ a large social experiment combined with register-based data allowing for up to 12-year follow-up to evaluate a long-lasting employer-sponsored health and well-being program. We show that employees at treated worksites receive fewer consultations from their primary care physician and purchase fewer prescription drugs. These effects persist up to seven years after randomization, though with some fade-out. We find no effects on overall hospitalizations, neither in the short or longer run, and the program was not successful in improving labor-related outcomes such as absence and turnover. Finally, we show some evidence of spillovers within the family.
Keywords: I12; I18; 330; worksite health program; health outcomes; labor outcomes; social experiment